2021
DOI: 10.21037/qims-20-1347
|View full text |Cite
|
Sign up to set email alerts
|

A rare acute neck pain cause that can have misdiagnosis or missed diagnosis-crowned dens syndrome: description of two cases and a literature analysis

Abstract: rare acute neck pain cause that can have misdiagnosis or missed diagnosis-crowned dens syndrome: description of two cases and a literature analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…A case report by Oka et al summarized 69 cases from previous case reports and reported that in 50% of cases, the initial diagnosis was wrong. 5 Meanwhile, more than 30 case reports and clinical images have been published since 2010, [6][7][8][9][10][11][12][13][14] and CDS is frequently mentioned in Japanese medical books. We have the impression that we regularly diagnose and manage CDS, suggesting a perception gap between these previous studies and our clinical experience.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A case report by Oka et al summarized 69 cases from previous case reports and reported that in 50% of cases, the initial diagnosis was wrong. 5 Meanwhile, more than 30 case reports and clinical images have been published since 2010, [6][7][8][9][10][11][12][13][14] and CDS is frequently mentioned in Japanese medical books. We have the impression that we regularly diagnose and manage CDS, suggesting a perception gap between these previous studies and our clinical experience.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, more than 30 case reports and clinical images have been published since 2010, 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 and CDS is frequently mentioned in Japanese medical books. We have the impression that we regularly diagnose and manage CDS, suggesting a perception gap between these previous studies and our clinical experience.…”
Section: Introductionmentioning
confidence: 99%
“…Lesion structure between individuals exhibits a vast difference. Furthermore, even within the same human body, there is a considerable degree of variability in the morphology of tissues, and similarities between lesion tissues and normal tissues can be observed, easily leading to misdiagnosis and missed diagnosis [15]. 6.…”
mentioning
confidence: 99%